LEKSIKON KEGULMAAN PADA MASYARAKAT JAWA DI PERKEBUNAN FAJAR AGUNG, KECAMATAN PEGAJAHAN, KABUPATEN SERDANG BEDAGAI: KAJIAN EKOLINGUISTIK (THE LEXICON OF WEEDS IN THE JAVANESE COMMUNITY AT FAJAR AGUNG PLANTATION, PEGAJAHAN DISTRICT, SERDANG BEDAGAI REGENCY: ECOLINGUISTIC STUDY) - Wiradi Putra; Dwi Widayati; Dardanila Dardanila (Balai Bahasa Jawa Barat, 2021)
The Javanese people of Fajar Agung Plantation (JPFAP) are workers who are very familiar with the lexicons of weeds. It can be seen from their sustainability until today as the way of preventing it from extinction. This writing aims to describe the level of the Javanese’ understanding of the lexicon of weeds in Fajar Agung Plantation and to explain the influencing factors using a qualitative approach which is supported by the quantitative calculation of the respondents. The data of the lexicon were obtained through a questionnaire which was listed through an interview with the key informants. The results shows that the list consists of 75 lexicons. Based on the first discussion, the level of understanding T (Tahu) for age group I (25—45 years) is 83.53% and age group II (46—60 years) is 83.15%. It means that the Javanese people in Fajar Agung Plantation still recognize and the lexicons in Javanese. Based on the second discussion, there are two factors affecting their level of understanding, namely linguistics and nonlinguistics factors. The linguistic factors is their tendency towards Javanese language. The nonlinguistic factors are their conservative behavior towards weeds, the physiological adaptation of weeds to herbicides, the consistency in the use of traditional weed control and eradication tools, the JPFAP welfare, the JPFAP education.